1998
DOI: 10.1002/(sici)1520-6823(1998)6:5<199::aid-roi1>3.3.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

RSR13, a synthetic allosteric modifier of hemoglobin, as an adjunct to radiotherapy: Preliminary studies with EMT6 cells and tumors and normal tissues in mice

Abstract: SUMMARY RSR13, 2[4-[[(3,5Dimethylanilino)carbonyl]methyl]phenoxy]-2-methylpropionic acid, a synthetic allosteric modifier of hemoglobin, reduces the affinity of hemoglobin for oxygen. The experiments reported here examined the effect of treatment with RSR13, combined with oxygen breathing, on the radiation response of EMT6 mammary tumors in BALB/c mice and of two normal tissues. RSR13 plus oxygen breathing increased the response of EMT6 tumors to irradiation. RSR13 had no discernible effects on tumors rendered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…A number of single-dose studies have shown that efaproxiral plus oxygen breathing increases the delivery of oxygen to hypoxic tumors and that this increase in tumor oxygenation enhances the effectiveness of radiotherapy (14,15). Efaproxiral plus oxygen breathing increased the effectiveness of radiation on EMT6 mammary tumors in BALB/c mice and reduced the hypoxic fraction to 9% from 24% found in either air-breathing or oxygen-breathing mice (16). When administered on days 4 through 18 after tumor implantation, efaproxiral was a highly effective an-219 EFAPROXIRAL, RADIATION AND OXYGENATION IN MURINE TUMORS timetastatic agent in animals bearing Lewis lung carcinoma (17).…”
Section: Introductionmentioning
confidence: 99%
“…A number of single-dose studies have shown that efaproxiral plus oxygen breathing increases the delivery of oxygen to hypoxic tumors and that this increase in tumor oxygenation enhances the effectiveness of radiotherapy (14,15). Efaproxiral plus oxygen breathing increased the effectiveness of radiation on EMT6 mammary tumors in BALB/c mice and reduced the hypoxic fraction to 9% from 24% found in either air-breathing or oxygen-breathing mice (16). When administered on days 4 through 18 after tumor implantation, efaproxiral was a highly effective an-219 EFAPROXIRAL, RADIATION AND OXYGENATION IN MURINE TUMORS timetastatic agent in animals bearing Lewis lung carcinoma (17).…”
Section: Introductionmentioning
confidence: 99%
“…RSR4 was a stronger effector than RSR13 in Hb solution studies and about equipotent in whole blood studies. [13][14][15][16][17] However, RSR13 was chosen as the candidate for phase I clinical trials with the rationale that the phenyl methyl substitution might be better tolerated in vivo in animal studies. This proved to be correct.…”
Section: Introductionmentioning
confidence: 99%
“…This pharmacodynamic (PD) effect is measured either as a decrease in standard cutaneous pulse oximetry (SpO 2 ) or as an increase in the partial pressure of O 2 (pO 2 ) to produce 50% saturation of Hb (p50). Nonclinical pharmacology (Khandelwal et al, 1996;Teicher et al, 1996;Rockwell and Kelley, 1998;Amorino et al, 2001) studies have demonstrated that efaproxiral can enhance the oxygenation of hypoxic tumours and function as a radiation sensitiser, increasing the effectiveness of RT.…”
mentioning
confidence: 99%